ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP: LITERATUR REVIEW - Bernardus Banda; Gita Meilana Fransiska (CV. ADIBA AISHA AMIRA, 2025)
Quality of service is a fundamental factor in influencing inpatient satisfaction in hospitals. This study aims to explore the impact of various service quality dimensions on inpatient satisfaction through a systematic literature review of ten studies conducted in different hospitals in Indonesia. The review shows that all five SERVQUAL dimensions—reliability, responsiveness, assurance, empathy, and tangibles—have a positive effect on patient satisfaction. Among them, assurance and empathy were identified as the most influential dimensions. These findings suggest that hospitals should prioritize the development of professional and empathetic healthcare staff in order to enhance service quality and patient satisfaction.